Bauxite industries: lesson learn from governance perspective - Mohd Tamizi, Mazlan; Khairil Anuar, Ramly; Nur Emilia, Abdullah Harun (KnE Social Sciences, 2019)
The mining of bauxite in Malaysia, specifically in Kuantan Pahang is in-demand industry. Over the last three years, Bauxite has become a national issue where uncontrolled handling will lead to severe impacts on the environment and the local community. It started from the dumping of bauxite by miners who have illegally and uncontrollably mine the bauxite. Thus, this paper aimed to study on good governance perspective as it is an important element in ensuring the sustainability of an organization and strengthening the direction and objectives of business activity. Failure to set effective good governance will cause the organization to be in a volatile state and will lead to fraud and breach of trust. The impact of these governance failures is huge and may cause the company or organization to be adversely affected and will cause negative perceptions from the community and stakeholders. This has led the government to set a moratorium to stop the bauxite operations. Throughout the moratorium, the Water, Land, and Natural Resources Minister revisits every single process and SOP to ensure that all rules and regulations, procedures, and laws are in full application. This paper looks at a lesson that can be learned from the episode and hopes it will serve as a guide to be the best steps to be taken to ensure that governance upheld once Bauxite activity continues.